(untitled) (Journal of Informatics Education and Research, 2026)
The telecommunications sector has become highly competitive, making customer satisfaction a key factor for the success of telecom companies. In addition to basic services such as voice calls and internet connectivity, telecom service providers new offer various value-added services to enhance customer experience and retain customers. The present study aims to examine the role of value-added services in enhancing customer satisfaction among telecom users in the selected cities of Junagadh, Rajkot, and Jamnagar. The study is based on a quantitative research design. Primary data were collected from 150 telecom customers using a structured questionnaire. The data were analyzed using statistical techniques such as percentage analysis, mean and standard deviation, correlation, and regression analysis to understand the relationship between value-added services and customer satisfaction. The findings of the study reveal that value-added services such as OTT subscriptions, data rollover, and security and spam protection services play a significant role in improving customer satisfaction. The results also indicate a positive relationship between value-added services and customer loyalty, as satisfied customers are more likely to continue using the same telecom service provider. The study concludes that effective and customer-oriented value-added services can significantly enhance customer satisfaction and provide a competitive advantage to telecom companies in the selected cities.